Risk of extracolonic cancers for people with biallelic and monoallelic mutations in MUTYH. Issue 7 (2nd June 2016) - Win, Aung Ko; Reece, Jeanette C.; Dowty, James G.; Buchanan, Daniel D.; Clendenning, Mark; Rosty, Christophe; Southey, Melissa C.; Young, Joanne P.; Cleary, Sean P.; Kim, Hyeja; Cotterchio, Michelle; Macrae, Finlay A.; et al.
Abstract : Germline mutations in the DNA base excision repair gene MUTYH are known to increase a carrier's risk of colorectal cancer. However, the risks of other (extracolonic) cancers for MUTYH mutation carriers are not well defined. We identified 266 probands (91% Caucasians) with a MUTYH mutation (41 biallelic and 225 monoallelic) from the Colon Cancer Family Registry. Mutation status, sex, age and histories of cancer from their 1, 903 first‐ and 3, 255 second‐degree relatives were analyzed using modified segregation analysis conditioned on the ascertainment criteria. Compared with incidences for the general population, hazard ratios (HRs) (95% confidence intervals [CIs]) for biallelic MUTYH mutation carriers were: urinary bladder cancer 19 (3.7–97) and ovarian cancer 17 (2.4–115). The HRs (95% CI) for monoallelic MUTYH mutation carriers were: gastric cancer 9.3 (6.7–13); hepatobiliary cancer 4.5 (2.7–7.5); endometrial cancer 2.1 (1.1–3.9) and breast cancer 1.4 (1.0–2.0). There was no evidence for an increased risk of cancers at the other sites examined (brain, pancreas, kidney or prostate). Based on the USA population incidences, the estimated cumulative risks (95% CI) to age 70 years for biallelic mutation carriers were: bladder cancer 25% (5–77%) for males and 8% (2–33%) for females and ovarian cancer 14% (2–65%). The cumulative risks (95% CI) for monoallelic mutation carriers were: gastric cancer 5% (4–7%) for males and 2.3% (1.7–3.3%) for females; hepatobiliary cancer 3% (2–5%) for males and 1.4% (0.8–2.3%) for females; endometrial cancer 3% (2%–6%) and breast cancer 11% (8–16%). These unbiased estimates of both relative and absolute risks of extracolonic cancers for people, mostly Caucasians, with MUTYH mutations will be important for their clinical management. Abstract : What's new? People who have a mutation in the MUTYH gene have an increased risk of colorectal cancer. But are they also at higher risk for other types of cancer? In this study, the authors found that people with one mutated copy of MUTYH (monoallelic) have an increased risk of gastric, liver, breast and endometrial cancers, while people with two mutated copies (biallelic) have an increased risk of bladder and ovarian cancers. This information will be useful for risk assessment in patients and families who carry MUTYH mutations.